TRANSAKSI PERBANKAN MELALUI INTERNET BANKING - Asuan, Asuan (Solusi, 2019)
Internet banking is one of the bank's services to customers to obtain information, communicate and conduct banking transactions through the internet network, the implementation of which customers already have a bank account, ATM and User ID and PIN to conduct banking transactions through internet banking based on article 1320 and 1338 Civil Code. Act Number 10 of 1998 concerning Banking in article 5 concerning types of banks, namely commercial banks and people's credit banks and article 40 regarding bank secrecy, including matters of banking transactions through internet banking and legal protection provided by banks regarding the confidentiality of customer data. Disputes on banking transactions through internet banking (banks and debtors) can be resolved by referring to agreements agreed upon by the parties, dispute resolution can be done through court (litigation) or outside the court (non-litigation) based on Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution in article 6 concerning general disputes that can be resolved through arbitration.